Zastrta znamenja - Maver, Aleš (Annales. Series historia et sociologia, 2017)
The paper discusses the question of dissident behaviour of representatives of the Catholic Church in Slovenia during the second half of 1970s, whereby the main attention is paid to the examination of texts published in the Catholic magazine Znamenje ("Sign") founded in 1971. In the fi rst part, the foundations and historical context of the "Ostpolitik" pursued especially by the Pope Paul VI and his Secretary of State Agostino Casaroli are explained. Some comparisons regarding the position of the Catholic Church in different Central and Eastern European environments are drawn as well. The authors argue that, in general, the Vatican "Ostpolitik" of the 1970s, bringing different forms of appeasement in relationship to the socialist states of Central and Eastern Europe (most notably represented by the "normalization" of the said relationship between the Holy See and Yugoslavia) mainly benefi ted the Church hierarchy, but did not substantially change (sometimes even increasingly diffi cult) position of common believers. The second part is dedicated to the analysis of some crucial texts, published in the magazine Znamenje, generally between 1975 and 1979, until after the papal election of John Paul II. The question, whether any form of alternative cultural or even political vision to the state sponsored socialist model could be traced in the magazine during the said period, is main focal point of the author's analysis. It can be shown that cases of an outspoken dissidence are very rare. This can be attributed to various factors, including system limitations together with a self-imposed censorship and structure of contributors, since great part of them were followers of the Christian socialist current in Slovenian Catholicism. Nevertheless, the magazine pretty vigorously opposed the alleged "atheisation" of society, especially in the area of education. On the other hand, contributors frequently denounced (historical) currents in Slovenian Catholicism which had prevailed before the World War II. Hence, contributors of the magazine somehow also curtailed a possible base for the development of alternative cultural models which were at least to some degree maintained visible from publications of the Catholic Church in Croatia in the same period. Similarly, the magazine closely followed the offi cial Yugoslav line in foreign politics, e. g. emphasizing developments in non-aligned countries and sympathizing with currents in Italian Catholicism of the 1970s advocating cooperation with communists.
Keywords: Catholic Church (Slovenia); Central Intelligence Agency; cerkev in država; church and state; disidentstvo; dissidence; Katoliška cerkev (Slovenija); Služba državne varnosti; Znamenje (periodicals); Znamenje (periodika)